Das andere Lesen Das Lesen multikodaler Textualität an Einfach(st)arbeitsplätzen im Spiegel der Relation aus Bildung und Teilhabe - Basendowski, Sven (Literalität und Arbeitswelt, 2020)
With the cultural-scientific approach of cultural techniques as a set of social literary practices, a theoretically critical and empirical study (mixed-methods study) is used to question which reading competencies mark the relation of education to fundamental participation in the work of socially disadvantaged young people to young adults. The theoretical discussion ranges from an analysis of cultural concepts in different reading approaches to the linguistic decomposition of the explored multi-codal textuality at a choice of examined simple workplaces - which grant a certain degree of social security and safe participation in work for the target group. The empirical findings of the mixed-methods study include, inter alia, the situational role of reading of the multi-codal textuality, along with the relevance of their application as knowing how in processing. The overall key message of the study is a critical view on the external validity of mainstream concepts of reading skills along with codality and social role of the underlying textuality: These mainstream concepts have a blind spot in the probabilistically prognostic significance of their functional minimum level for professional success in terms of an (inclusive) education system. Dr. phil. Sven Basendowski teaches as a junior professor at the university of Rostock at the institute for special educational development and rehabilitation. His main areas of work/interest are the cultural-technical and vocationally oriented educational processes under precarious conditions, network-analytical consideration of social disadvantage, structures of the transitional regimes school/work in the mirror of social disadvantage as well as their subject-oriented treatment.